Bluffing in labor negotiations: Legal and ethical issues - Carson, Thomas L. (Journal of business ethics, 1982)
This paper presents an analysis of bluffing in labor negotiations from legal, economic, and ethical perspectives. It is argued that many forms of bluffing in labor negotiations are legal and economically advantageous, but that they typically constitute lying. Nevertheless it is argued that it is generally morally acceptable to bluff given a typical labor-management relationship where one's negotiating partner is familiar with and most likely employing bluffing tactics him/herself. We also consider whether it is an indictment of our present negotiating practices and our economic system as a whole that, given the harsh realities of the marketplace, bluffing is usually morally acceptable.